2022
DOI: 10.1108/meq-10-2021-0251
|View full text |Cite
|
Sign up to set email alerts
|

Financial development–ecological footprint nexus in Malaysia: the role of institutions

Abstract: PurposeMotivated by the conflicting evidence on the effect of financial development on environmental quality, this study investigates the moderating role of institutional quality in the link between financial development and environmental quality using a robust proxy in Malaysia from 1984 to 2017.Design/methodology/approachEcological footprint is used to measure environmental quality, while financial development is proxied using three measures (domestic credit provided by the private sector, domestic credit pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 98 publications
4
46
0
Order By: Relevance
“…In contrast, the adverse effect of trade on CO 2 emissions was disentangled by EddineChebbi et al (2011). A consistent conclusion has been reached byDada et al (2022a) andDou et al (2021).2.6 Environmental degradationtotal energy consumption nexusA notable share of fossil fuel composition in the total primary energy consumption always hurts the environmental quality(Mahalik et al, 2021). Moreover, environmentalists and agencies of environmental protection consider energy use as the primary driver of pollution.…”
mentioning
confidence: 86%
“…In contrast, the adverse effect of trade on CO 2 emissions was disentangled by EddineChebbi et al (2011). A consistent conclusion has been reached byDada et al (2022a) andDou et al (2021).2.6 Environmental degradationtotal energy consumption nexusA notable share of fossil fuel composition in the total primary energy consumption always hurts the environmental quality(Mahalik et al, 2021). Moreover, environmentalists and agencies of environmental protection consider energy use as the primary driver of pollution.…”
mentioning
confidence: 86%
“…Murshed et al 33 discovered that for South Asian countries that regional integration of trade mitigates the effusion of carbon dioxide. Contrarily, Dada et al 5 found that openness in trade increases carbon effusions in Nigeria using the ARDL technique. Examining the environment-trade nexus of non-OECD and OECD countries, Cole 34 validated the "pollution haven" hypothesis.…”
Section: Carbon Emissions and Trade Opennessmentioning
confidence: 99%
“…Lastly for the growth and conservation hypothesis, it proposes that there is a unidirectional relationship that is confirmed by several researches such as Fodha and Zaghdoud 76 for Tunisia and Menyah and Wolde-Rufael 77 for South Africa. Dada et al 5 found that economic growth increases effussions of CO 2 in Nigeria using ARDL technique.…”
Section: Carbon Emissions and Gdpmentioning
confidence: 99%
“…This confirms the findings of the correlation analysis. The reduction in environmental quality resulting from the shadow economy defies the findings of the majority of empirical studies (Dada et al, 2022c(Dada et al, , 2022dDada et al, 2021a;Pang et al, 2022;Huynh, 2020;Chen et al, 2018). The following are a few reasons why the shadow economy is beneficial to the environment in Africa.…”
Section: Impact Of Income Inequality Shadow Economy On Environmental ...mentioning
confidence: 99%
“…Existing studies suggest that the shadow economy is among the factors affecting environmental degradation. For instance, the shadow economy study of Dada et al (2022cDada et al ( , 2022d in relation to the environment reveals the adverse damages to environmental quality through the informal economy. Ajide (2021) shows that shadow economy is being affected by financial inclusion.…”
Section: Literature and Hypothesesmentioning
confidence: 99%